Sizing Up the Impact of Embassies on Exports - Shon Ferguson; Rikard Forslid (Research Institute of Industrial Economics (IFN), 2014)
The purpose of this study is to test for the effects of trade promotion via the foreign service. We develop a Melitz-based model where firms are heterogeneous with respect to productivity and must pay a beachhead cost to enter a foreign market, which can be reduced by government spending on trade promotion. The model predicts that unilateral trade promotion allows medium-sized firms to export. We test this prediction using Swedish firm-level data and information on the opening and closing of Swedish embassies abroad using Norwegian firms as control group. Our results lend support to the predictions of the model, with large and medium-sized firms responding most strongly to the opening of embassies.
Keywords: D21; D22; F12; F15; 330; Heterogeneous firms; Trade promotion